2020
DOI: 10.21203/rs.2.17973/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DKK3 attenuates JNK and AP-1 induced inflammation via Kremen-1 and DVL-1 in mice following intracerebral hemorrhage

Abstract: Background: Intracerebral hemorrhage (ICH) is the most devastating stroke subtype, with a poor prognosis and few proven treatments. Neuroinflammation is associated with ICH-induced brain injury and unfavorable outcomes. There is growing evidence that Dickkopf (DKK) 3 plays a key role in the adaptive anti-inflammatory and neuroprotective responses following intracerebral hemorrhage. This study aimed to evaluate the protective effects of DKK3 against brain edema and neuroinflammation in a mice model of ICH. Metho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The mass effect of intracerebral hematoma as well as red blood cell debris and degradation products are considered to be key factors leading to early brain injury following ICH [ 7 – 9 ]. As a consequence, a complex inflammatory cascade leads to brain edema, blood–brain barrier (BBB) disruption, neuronal apoptosis in the perihematoma area, and other unfavorable outcomes [ 10 , 11 ]. Therefore, the development of therapies that target anti-inflammatory and anti-apoptotic pathways may be crucial to improving neurological outcomes following ICH.…”
Section: Introductionmentioning
confidence: 99%
“…The mass effect of intracerebral hematoma as well as red blood cell debris and degradation products are considered to be key factors leading to early brain injury following ICH [ 7 – 9 ]. As a consequence, a complex inflammatory cascade leads to brain edema, blood–brain barrier (BBB) disruption, neuronal apoptosis in the perihematoma area, and other unfavorable outcomes [ 10 , 11 ]. Therefore, the development of therapies that target anti-inflammatory and anti-apoptotic pathways may be crucial to improving neurological outcomes following ICH.…”
Section: Introductionmentioning
confidence: 99%
“…Brain samples were collected 24 h after MCAO. Western blotting was performed as described previously [35]. The proteins of right hemispheres were extracted by cytoplasmic extraction reagents (Pierce Biotechnology, Rockford, IL, USA).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Several lines of investigation revealed that JNK plays important roles in neuronal inflammation under in vivo conditions. Furthermore, it has reported that increased p-JNK activation mainly disturb the antioxidant defense mechanism and subsequently initiates neuroinflammatory and neurodegenerative cascades [15,36,37]. To evaluate the chronic ischemic condition effects on neuroinflammation, we analyzed the activated p-NF-κB and the expression level of proinflammatory cytokines such as TNF-α, IL-1β, and NOS2 in the ipsilateral cortex and hippocampus of the ischemic brain.…”
Section: Chronic Ischemia Induces Neuroinflammatory Cascades In Ipsilateral Cortex and Hippocampus Of The Adult Mousementioning
confidence: 99%